2017
DOI: 10.1161/hypertensionaha.116.08814
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Heterodimerization and Functional Interaction of the Angiotensin Type 2 Receptor and the Receptor MAS

Abstract: The angiotensin type 2 receptor (AT2R) and the receptor MAS are receptors of the protective arm of the renin-angiotensin system. They mediate strikingly similar actions. Moreover, in various studies, AT2R antagonists blocked the effects of MAS agonists and vice versa. Such cross-inhibition may indicate heterodimerization of these receptors. Therefore, this study investigated the molecular and functional interplay between MAS and the AT2R. Molecular interactions were assessed by fluorescence resonance energy tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 49 publications
5
93
0
Order By: Relevance
“…This notion is supported by our recent FRET studies in HEK cells expressing AT 2 R and MasR that their agonists alone do not affect FRET suggesting that these ligands do not promote or dissociate dimerization. 29 Along the same line of notion, other studies suggested that pretreatment of agonist or antagonist did not affect interactions of AT 2 R with AT 2 R, 36 AT 1 R 40 or B 2 R. 41 …”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…This notion is supported by our recent FRET studies in HEK cells expressing AT 2 R and MasR that their agonists alone do not affect FRET suggesting that these ligands do not promote or dissociate dimerization. 29 Along the same line of notion, other studies suggested that pretreatment of agonist or antagonist did not affect interactions of AT 2 R with AT 2 R, 36 AT 1 R 40 or B 2 R. 41 …”
Section: Discussionmentioning
confidence: 89%
“…36 Leonhardt and co-workers recently suggested that C35 of AT 2 R is essential for AT 2 R-MasR heterodimerization as FRET efficiency was found significantly decreased in HEK-293 cells transiently transfected with vectors encoding mutant AT 2 R-C35A-YFP and nonmutant MAS-CFP. 29 Particularly, Cys35 of the N terminus in one and Cys290 of exoloop 3 of other AT 2 R played a role in constitutive homodimerization of AT 2 R via disulfide bridge formation. 36 Another study demonstrated that deletion of residues 240–244 within intermediate portion of cytoloop 3 resulted in a complete loss of AT 2 R-mediated effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, there have been no studies which have assessed the cellular co-expression of Mas and AT2R in brain cardiovascular control centers. Nonetheless, a very recent article demonstrates dimerization between Mas and AT2R [54], and so their potential cooperation at the receptor level to lower blood pressure cannot be excluded.…”
Section: Open Questionsmentioning
confidence: 99%